Pengaruh Profitabilitas, Leverage, Porsi Kepemilikan Saham Publik Dan Ukuran Dewan Komisaris Terhadap Pengungkapan Corporate Social Responsibility Dalam Laporan Tahunan Perusahaan Food & Beverages Yang Listing Di Bursa Efek Indonesia - Lamia, Fathia Vivie; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to empirically examine the effect of profitability, leverage, the portion of public ownership and board size on corporate social responsibility disclosure coorporateThe population of this study are Food & Beverages company listed in Indonesia Stock Exchange (2009-2012). The sample is part of the number and characteristics possessed by the population. The sample selection was conducted using purposive random sampling as many as 18 companies. Data analysis in this study uses regression analysis is basically the study of the dependence of the dependent variable (bound) with one or more independent variables (explanatory variables / bound)Based on the first hypothesis indicates that there is a partial significant effect of CSR Disclosure profitability. Under the second hypothesis indicates that there is a partial significant effect of leverage on CSR Disclosure. Under the third hypothesis indicates that the partial there is significant influence between the Public Shareholding Portion CSR Disclosure in Companies Food and Beverage. Based on the fourth hypothesis indicates that there is no partial significant effect between the size of the Board of Commissioners on CSR Disclosure in Companies Food and Beverage. Based on the above calculation values obtained coefficient of determination (R2) of 0.371. This suggests that the Profitability, Leverage, Public Shareholding Portion, Size BOC and CSR simultaneously providing 37.10% of the effect of CSR disclosure.Keywords: Profitability, Leverage, Public Shareholding Portion Size BOC and Disclosure of Corporate Social Responsibility